Studying Interaction Design as an English Education Student for the Indonesian International Student Mobility Award (IISMA) in New Zealand: A Case Study in English Speaking Country - Alia Fitrida Camila; Arafiq; Dewi Satria Elmiana (Journal of English Education Forum (JEEF), 2023)
This journal provides an account of the encounters of an International Student Mobility Awards (IISMA) awardee who majoring English education and undertook a multidisciplinary Interaction Design course at Victoria University of Wellington, New Zealand. The journal employs a series of learning techniques applied during a single trimester of the educational journey in New Zealand within the Interaction Design class. The result is that students experience an increase in skills and knowledge in designing and analyzing User Experience (UX) to create useful and creative products. These skills and knowledge will be useful for students as an English language education student who have to create interesting learning media in the future.